DEDDIAG, a domestic electricity demand dataset of individual appliances in Germany - Marc Wenninger (Nature Portfolio, 2021)
Measurement(s) domestic appliance electricity usage • whole-house mains reading • ground truth event annotations Technology Type(s) energy measurement system • Annotation Sample Characteristic - Environment house Sample Characteristic - Location Germany Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.14753556